Transformasi Pendidikan Islam Melalui Motivasi Religiopedagogis Guru Interdisipliner Dalam Pembelajaran TPQ Di MI Muhammadiyah 1 Kota Probolinggo - Indriawati, Mukti Peni; Khoiriyah, Khoiriyah (Educational Research Center, 2026)
TPQ (Qur’anic learning) in Islamic elementary schools ideally requires teachers with strong Tahsin and tajwid proficiency, sound pedagogy, and consistent spiritual guidance. At MI Muhammadiyah 1 Probolinggo, however, most cross subject teachers are assigned to teach TPQ, resulting in uneven instructional quality. This qualitative study employed an intrinsic case study design to (1) map TPQ practices among interdisciplinary teachers and identify dominant challenges in tajwid and tilawah, classroom management, and assessment; (2) describe teachers’ religio-pedagogical motivation (worship orientation, professional trustworthiness or amanah, learner centered compassion or rahmah, and commitment to competence development and its links to instructional quality; and (3) examine the effects of targeted mentoring on teachers’ instructional competence and students’ tilawah and tajwid achievement and participation over one semester. Data were collected through in depth interviews (teachers, school leaders, parent or student representatives), classroom observations, and document analysis; thematic analysis followed open axial selective coding and was strengthened through triangulation, member checking, and an audit trail. The targeted mentoring was implemented through school-based mechanisms involving the principal, the TPQ coordinator, and peer teachers, while the researcher acted as a reflective facilitator and a limited participant observer who documented changes in instructional practices. Findings indicate that early challenges centered on inconsistent tajwid feedback, limited differentiation in heterogeneous classes, and assessment practices emphasizing reading quantity over improvement processes and murajaah habits. Religiopedagogical motivation acted as a lever of change: worship orientation and amanah supported persistence and consistency, rahmah enhanced learning comfort and students’ confidence to read, and competence-development commitment increased openness to improvement. Targeted mentoring strengthened method consistency, feedback quality, murajaah discipline, and student participation. This study operationalizes religio-pedagogical motivation and proposes a scalable, tiered mentoring model for TPQ quality improvement in interdisciplinary teaching contexts.